On the modernization of systems for supporting digital transformation: A research agenda - Leon, Pablo Luiz; Horita, Flávio Eduardo Aoki (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Digital transformation is changing the attitudes of companies to creating value for customers and, this requires making alterations in their working models, organizational structure and technological systems. However, companies have either legacy systems or monolithic systems, which raises a complex problem since there is a need for technological adaptability to meet the commercial demand for the creation of new digital products or services. In this context, this article conducts a systematic mapping study to assess how far the current literature investigates modernized systems that enable digital transformation to take place in companies. The results suggest there is a conspicuous gap with regard to studies that explore modernization models with integrated systems, or can ensure these systems can evolve without compromising the business. The study also finds gaps in the examination of methods or architectural models, which allow modernized systems to evolve gradually without interrupting the business activities.